BERPIKIR KREATIF SISWA KELAS X SEKOLAH MENENGAH ATAS MUJAHIDIN PONTIANAK TAHUN 2018 - Liliana Liliana; Mohammad Asrori; Yuline Yuline (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract Creative learning in students on their own has been owned by each student itself, only their order in terms of experience and thinking of the utilization of this creativity does not run as optimally. Therefore, researchers want to know more about the creative thinking of tenth grade students of Pontianak High School Mujahidin. The problem in this study was "How to think creatively in the tenth grade students of Pontianak High School Mujahidin?". This study aimsed to obtain an overview of creative thinking of tenth grade students of Pontianak High School Mujahidin. The method used is descriptive method and the form of research was survey studies. The population in this study were 33 grade X students of Pontianak High School Mujahidin. This study used a quantitative approach. Data collection techniques used are indirect communication techniques with data collection tools in the form of questionnaires. While the data analysis technique used percentage calculations.Based on the results of data analysis from creative thinking research Class X Mujahidin High School of Pontianak students obtained 71% of the results of lateral creative thinking in the "High" category.Keywords: Creative thinking students